A physician-pharmacist collaborative care model to prevent opioid misuse. (21st April 2020) - Lagisetty, Pooja; Smith, Alex; Antoku, Derek; Winter, Suzanne; Smith, Michael; Jannausch, Mary; Mi Choe, Hae; Bohnert, Amy S B; Heisler, Michele
Abstract: Purpose: Clinical pharmacists in primary care clinics can potentially help manage chronic pain and opioid prescriptions by providing services similar to those provided within their scope of practice to patients with diabetes and hypertension. We evaluated the feasibility and acceptability of a pharmacist-physician collaborative care model for patients with chronic pain. Methods: The program consisted of an in-person pharmacist consultation and optional follow-up visits over 4 months in 2 primary care practices. Eligible patients had chronic pain and a long-term prescription for opioids or buprenorphine or were referred by their primary care physician (PCP). Pharmacist recommendations were communicated to PCPs via the electronic medical record (EMR) and direct communication. Mixed-methods evaluation included baseline and follow-up surveys with patients, EMR review of opioid-related clinical encounters, and provider interviews. Results: Between January and October 2018, 47 of the 182 eligible patients enrolled, with 46 completing all follow-up; 43 patients (91%) had received opioids over the past 6 months. The pharmacist recommended adding or switching to a nonopioid pain medication for 30 patients, switching to buprenorphine for pain and complex persistent opioid dependence for 20 patients, and tapering opioids for 3 patients. All physicians found the intervention acceptable but wanted more guidance on prescribing buprenorphine for pain. Most patients found the intervention helpful, but some reported a lack of physician follow-up on recommended changes. Conclusion: The study demonstrated that comanagement of patients with chronic pain is feasible and acceptable. Policy changes to increase pharmacists' authority to prescribe may increase physician willingness and confidence to carry out opioid tapers and prescribe buprenorphine for pain.